The Implementation of Assessment Instant Strategy in Increasing of Akidah Akhlak Learning Outcomes on Class VII-B at Material of Blessed Behavior in MTs-Islamic Boarding School Al-Kahfi Subdistrict Bangun Purba Regency Rokan Hulu-Riau - Bashori Bashori (Pusat Penerbitan Universitas (P2U) Unisba, 2017)
Abstract The purpose of this study is to find out the implementation of strategies Assessment Instant in learning Akidah Akhlak of seventh-grade students in MTs of Islamic boarding school Al-Kahf Bangun Purba district Rokan Hulu. From the results of data analysis can be concluded that the survey results in Akidah Akhlas for class VII B on the subject of proper manner to fellow MTs PP. Al-Kahfi Bangun Purba of Rokan Hulu can be enhanced through the implementation of strategies Instant Assessment, in which the common learning outcomes of students of class VII B has increased from 70.83 in the prior action into 77.75 in the first cycle, and finally, reaches 82.75 in the second reporting period. From the test results obtained by the price to the hypothesis of 28.30 was greater than table good at the significance level of 5% (2.07) and 1% (2.81). Thus the alternative hypothesis (Ha) is acceptable. Keywords: Strategy, Instant Assesment, and Learning Result. Abstrak Tujuan penelitian ini adalah untuk mengetahui penerapan strategi Instanst Assesment dalam pembelajaran Akidah Akhlak siswa kelas VII B di MTs Pon-Pes Al-Kahfi Bangun Purba Kabupaten Rokan Hulu. Dari hasil analisis data dapat disimpulkan bahwa hasil belajar Akidah Akhlak siswa kelas VII B pada materi akhlak terpuji di MTs PP. Al-Kahfi Kecamatan Bangun Purba Kabupaten Rokan Hulu dapat ditingkatkan melalui penerapan strategi Instant Assesment, dimana rata-rata hasil belajar siswa kelas VII B mengalami peningkatan dari 70,83 pada sebelum tindakan menjadi 77,75 pada siklus I, dan akhirnya mencapai 82,75 pada siklus II. Dari hasil uji hipotesis diperoleh harga to sebesar 28,30 ternyata lebih besar dari ttabel baik pada taraf signifikan 5% (2,07) maupun 1% (2,81). Dengan demikian hipotesis alternatif (Ha) dapat diterima. Kata Kunci: Strategi, Instant Assesment, dan Hasil Belajar.